NEUROLYTIC SPLANCHNIC NERVE BLOCK WITH ALCOHOL FOR UPPER ABDOMINAL CANCER PATIENTS: A SYSTEMATIC REVIEW - Fitrisyah, Aidyl; Prawira, Nico Adithia; Friankasari, Devadiza (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
Pain is the most common symptom experienced by approximately 66% of patients with advanced, metastatic, or terminal cancer. Splanchnic nerve block with neurolytics can help reduce pain and is indicated for treating pain caused by malignant tumors in the retroperitoneum and upper abdomen. This systematic review used data from electronic databases (PubMed, ScienceDirect, ProQuest, and EPMC) to identify studies published in English between 2015 and 2025; five studies were included for review. Neurolytics with alcohol concentrations between 50% and 99.7% and injection volumes from 5 mL to >20 mL consistently provided significant pain reduction in patients with intra-abdominal pain due to cancer in the first three months. The potential for reducing opioid use and various techniques make splanchnic nerve neurolytics one of the therapeutic options in palliative pain management.